Genetic diversity, population structure and ancestral origin of KwaZulu-Natal native chicken ecotypes using microsatellite and mitochondrial DNA markers. Issue 1 (14th December 2020) - Nxumalo, Nkosinathi; Ceccobelli, Simone; Cardinali, Irene; Lancioni, Hovirag; Lasagna, Emiliano; Kunene, Nokuthula Winfred
Abstract: South African native chicken breeds are no exception to the declining of local domestic breeds that has long been recognised and found associated with the commercialisation of breeding in domestic animals. The aims of the study were: (i) to provide a comprehensive view of genetic variation in four KwaZulu-Natal indigenous chicken populations (Jozini, Newcastle, Pietermaritzburg, and Port Shepstone), and (ii) to estimate the extent of differentiation of the village populations from three conserved South African indigenous pure breeds (Potchefstroom koekoek, Ovambo, and Venda) by genotyping individuals at 19 autosomal microsatellite loci. Finally, (iii) new information to the history of KwaZulu-Natal indigenous chicken populations was made available by exploring their phylogenetic relationship and their possible maternal origin through the mitochondrial DNA. The results suggested noticeable genetic diversity within and between ecotypes with clear sub-structuring between them. The indigenous populations had high genetic diversity (observed heterozygosity ranging from 0.61 in Pietermaritzburg to 0.70 in Jozini) while conserved populations showed considerable within population inbreeding coefficient (from 0.01 in Potchefstroom koekoek to 0.18 in Ovambo). Median-joining network analyses indicated the dominance of haplogroup E suggesting a likely Southeast Asia and/or Indian subcontinent origin. The presence of haplogroup B and C not only emphasises multiple maternal origin but also highlights genetic introgression of local chickens with commercial genotypes. These results highlighted the importance of local breeds as a genetic reservoir; moreover, the conservation of local breeds may play an important role in the local economy as a source of high-quality products for consumers. Highlights: The genetic variation and differentiation of KwaZulu-Natal indigenous chicken populations and pure South African chicken breeds is investigated. The village populations showed a noticeable genetic variability with clear sub-structuring between them. The results can be used to improve a sustainable breeding and conservation programs to control possible genetic dilution with commercial genotypes.